AN EXISTENCE AND UNIQUENESS OF THE SOLUTION OF SEMILINEAR MONOTONE ELLIPTIC EQUATION WITH THE DATA IN STUMMEL CLASSES - Nicky Kurnia Tumalun (Barekeng)
Let  be a bounded open subset of , ,  be a function in Stummel classes , where , and